The Spirit of Feminism in the Novel Ancika Dia Yang Bersamaku Tahun 1995 By Pidi Baiq: The Spirit of Feminism in the Novel Ancika Dia Yang Bersamaku Tahun 1995 By Pidi Baiq - Iqbalva Demas; Onok Yayang Pamungkas (P3M IAI Nusantara Batang Hari, 2024)
This study represents an effort to investigate the feminist spirit within Pidi Baiq's novel